Whiptail lizard lineage delimitation and population expansion as windows into the history of Amazonian open ecosystems. Issue 8 (17th November 2021) - Martins, Lidia F.; Choueri, Erik L.; Oliveira, Alan F. S.; Domingos, Fabrícius M. C. B.; Caetano, Gabriel H. O.; Cavalcante, Vitor H. G. L.; Leite, Rafael N.; Fouquet, Antoine; Rodrigues, Miguel T.; Carnaval, Ana C.; Colli, Guarino R.; Werneck, Fernanda P.
Abstract : Historical variations in climate and landscape configuration are the main aspects known to generate and maintain diversity. Taxa associated with open habitats within broader forest contexts are often overlooked in studies of Neotropical biogeography. We investigated the evolutionary and demographic history of lizards in the Cnemidophorus lemniscatus species group, which encompasses three described species – one unisexual and two bisexuals – restricted to open environments in Amazonia. We also explored the geographic ecology of the group using critical ecophysiological traits as proxies for sensitivity or resilience to environmental change. To that end, we delimited the main lineages within the group, estimated their divergence times, and asked if these lineages have experienced changes in effective population size. We recovered six lineages, three of which correspond to C. cryptus, C. lemniscatus, and C. gramivagus, and three yet unnamed species. We recovered divergence events during the Late Miocene and signs of recent population expansion for at least one of the species (the parthenogenetic C. cryptus ). This pattern corroborates the ancient emergence of the Amazonian open areas, followed by a high and recent dynamism during the Pleistocene. Conserved traits related to high thermal tolerance and broad thermal tolerance ranges likely facilitated niche tracking and establishment in open ecosystems during Pleistocene climatic fluctuations. Our results bring insights regarding how these species might be influenced, and even favoured, by human-induced environmental changes in the contemporary timescale.